Effect of brewing method, time and concentration on the quality of coconut (Cocos nucifera Linn) coffee - Gabuat, Joanna M.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
The effects of varying brewing method, time, and concentration on the physico-chemical properties (pH, %TA, TSS, viscosity, color); intensity ratings (clarity, roasted aroma, coffee flavor, sweetness, bitterness, astringency, off-flavor); and consumer acceptance (color, aroma, flavor, overall) of brewed coconut coffee prepared from male coconut flowers were assessed. From three brewing methods (boiling, steeping, and coffee maker), steeping was selected as the best method because its flavor and overall acceptability were slightly higher than boiling, although both methods were of similar range. Viscosity was not affected by the type of brewing employed; while clarity, roasted aroma, and color acceptance were the only sensory attributes that showed significant difference (P<0.05). The effects of three brewing times (1, 5, and 10 min) and concentrations (7, 11, and 16% w/v) on the same parameters and attributes were further studied using response surface methodology. Coffee flavor and roasted aroma intensity ratings were used as basis for finding the optimum time and concentration combination. Brewing concentration of 11-16% w/v and at longer steeping times (5-10 mins) were shown to have higher ratings for the said parameters. Viscosity, off-flavor intensity, aroma, flavor, and overall acceptance did not show significant difference (P<0.05) among all treatments.
Thesis Classification: C
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Coconut -- Philippines; Coconut -- Processing; Coconut coffee